Gaya Komunikasi Mahasiswa Dalam Menyukseskan Program Magang Merdeka Belajar Kampus Merdeka Di Dinas Syariat Islam Kota Banda Aceh - Juhari Juhari (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2025)
This research is based on the phenomenon of imbalance between the academic world and the professional world, which tends to prioritize expertise and professionalism, while universities often emphasize academic abilities with various theories. The imbalance becomes the cause of the inability of university graduates to face competition in the workforce. This is what constitutes the implementation of internships. The research uses a qualitative approach with interview techniques. The research results show that on average, MBKM internship students at the Islamic Sharia Office of Banda Aceh City have been able to communicate well, allowing them to be accepted and blend in well. The communication process that occurs is still passive, meaning that students accept any tasks assigned by their superiors. The process of completing the assigned tasks is carried out through structured consultations, so their presence is seen as having contributed to the duties of state apparatus.